A Systematic Review of parent-adolescent interactions about sexuality in the African context - Mfenyana, Anelisa (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Research Objective: to analyse knowledge that has been presented in recently published articles on parent-adolescent sexuality interactions in the African context. Methods: The research is undertaken through a systematic review, using a specific Boolean search in the EBSCOhost database. After the search and screening processes, 27 articles published between 2000 and 2020 were included in the review. Results: The dominant theme across the reviewed papers was HIV in general and its prevention more specifically. This over-riding theme is dealt with accordingly to four main sub-themes, namely: parents' and adolescents' knowledge about HIV/AIDs; sexuality communication between parents and adolescents; the association between the aforementioned communication and adolescent sexual behaviour; and the effectiveness of numerous specific HIV prevention interventions. The vast majority of the reviewed papers use a mainstream theoretical framework and utilise quantitative research methods. Their findings and recommendations are in line with mainstream hypotheses and assertions about HIV prevention. Conclusions: Strong global institutional forces and power relations generate the mainstream knowledge contained in the published work considered in this review, and that this knowledge in turn further entrenches these power relations. It would be useful to conceptualise the dimensions and implications of an alternative, critical approach to HIV prevention and parent-adolescent sexuality communication as well as a more comprehensive approach to sexuality education (which includes more than knowledge transfer about preventing HIV).
Keywords: Psychology -- South Africa; Sex instruction for teenagers -- South Africa; Parent and teenager -- South Africa; Teenagers -- Sexual behavior -- South Africa; HIV infections -- Prevention; HIV (Viruses) -- South Africa; Communication and sex -- South Africa; Health risk communication -- South Africa; Systematic review